Implicações da prática de gestão fisco-tributária na educação básica brasileira: o caso do Município de Belford Roxo - RJ - Silva, Carlos Antonio Leite da (2016)
In this dissertation was researched, studied and discussed the tax authorities and tax Administration of direct municipal revenues, transfers and constitutional transfers from the state and the Union by the municipality of Belford Roxo and the application of these resources in basic education, which includes early childhood education, Education Elementary and high school. Preschool education is divided into: kindergarten and pre-school; Elementary School is divided into two levels: the first to the fifth year and the sixth to ninth grade and high school, with three-year, which was included in Basic Education in February 6, 2006 (Law 11.274 of February 6 2006). Direct Municipal Taxes considered in the study were the property tax, the ISSQ and Fees. As for transfers and constitutional transfers were included the property taxes, ICMS, IR, IPI, Royalty Oil, FUNDEF, FUNDEB and the FPM. Additionally were taken into account the constitutional principles such as the Transparency and Publicity, and the main Brazilian law as: Federal Constitution, the budget law, the Fiscal Responsibility Law and including the Education Accountability Act which is under study in National Congress. Regarding the Basic Education teaching major variables listed were those linked to quantitative schools, classrooms, faculty and staff; teachers and enrollment in early childhood education; teachers, enrollment, dropout and students in elementary school. And finally, indexes and notes used were IDEB, PISA, IFDM and the HDI.